2017
DOI: 10.1038/srep43108
|View full text |Cite
|
Sign up to set email alerts
|

Deep sequencing and transcriptome analyses to identify genes involved in secoiridoid biosynthesis in the Tibetan medicinal plant Swertia mussotii

Abstract: Swertia mussotii Franch. is an important traditional Tibetan medicinal plant with pharmacological properties effective in the treatment of various ailments including hepatitis. Secoiridoids are the major bioactive compounds in S. mussotii. To better understand the secoiridoid biosynthesis pathway, we generated transcriptome sequences from the root, leaf, stem, and flower tissues, and performed de novo sequence assembly, yielding 98,613 unique transcripts with an N50 of 1,085 bp. Putative functions could be ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 57 publications
4
34
0
Order By: Relevance
“…Sweroside (4), swertiamarin (5), and gentiopicrin (6) are reported as the most abundant secoiridoids from this family, and it is presumed that the biosynthetic pathway leading from 4 to 5 and 6 is universally present in the whole Gentianaceae family [36]. In some species, roots are the site of the highest SGs accumulation [37,38], while, in others, including C. erythraea, these compounds are more abundant in the above-ground parts [4,[39][40][41]. Furthermore, the content of total SGs in C. erythraea leaves is reported not to be significantly influenced by the developmental stage [4].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sweroside (4), swertiamarin (5), and gentiopicrin (6) are reported as the most abundant secoiridoids from this family, and it is presumed that the biosynthetic pathway leading from 4 to 5 and 6 is universally present in the whole Gentianaceae family [36]. In some species, roots are the site of the highest SGs accumulation [37,38], while, in others, including C. erythraea, these compounds are more abundant in the above-ground parts [4,[39][40][41]. Furthermore, the content of total SGs in C. erythraea leaves is reported not to be significantly influenced by the developmental stage [4].…”
Section: Resultsmentioning
confidence: 99%
“…Both of the genes are specifically involved in the iridoid branch and are under control of an amplification loop [28]. It is accepted that these two TFs are involved in the regulation of the structural genes expression in C. roseus that MYC2/ORCA3 cascade cannot cover [31,39]. Conversely, JAM1 and its homologues, JAM2 and JAM3, are negative regulators of MYC-like TFs and JA responses.…”
Section: Secoiridoids-related Biosynthetic Genes Expression Profiles mentioning
confidence: 99%
“…There was a significantly positive correlation ( p < 0.01) between loganic acid and sweroside in both leaves and roots from Dali. Biosyntheses of sweroside, gentiopicroside, and swertiamarin were found to rely on loganic acid whose creation mainly happens in leaves, as the precursor, according to most reports about ( seco -) iridoid pathway in recent years (Miettinen et al, 2014 ; Tham et al, 2016 ) However, discussing in the study associated with seco -iridoid biosynthesis in Swertia mussotii , Liu Y. et al ( 2017 ) indicated that gene expressions associated with synthesis were extremely low in roots except for one named Sm7DLGT responsible to the coding of 7-deoxyloganetic acid glucosyl transferase who catalyzes the reaction of producing 7-deoxyloganetic acid (loganic acid's precursor). Hua et al ( 2014 ) also hypothesized that seco -iridoids were transformed to the roots after finishing the synthesis in other tissues.…”
Section: Resultsmentioning
confidence: 99%
“…What's more, the positive correlation ( p < 0.05) was found between sweroside in stems and roots. However, while a large amount of gene related to the pathway express in leaves, there was not striking connection between gene expression profile and accumulation of ( seco -) iridoid glycosides in Gentianaceae plants (Courdavault et al, 2014 ; Luca et al, 2014 ; Liu Y. et al, 2017 ). Thus, information obtained from different organs in present work might reflect the transporting relationship in inter-tissues.…”
Section: Resultsmentioning
confidence: 99%
“…Tamura et al (2017) varied cytochrome P450 monooxygenases (P450s) function in triterpenoid saponin biosynthesis of Platycodon grandiflorus by the analysis of three different tissues (roots, leaves, and petals) using RNA sequencing (RNA-Seq) technology [ 21 ]. Ma et al (2016) and Liu et al (2017) analyzed the transcriptome of Swertia mussotii and screened 39 candidate transcripts involved in secoiridoid biosynthesis [ 22 ]. Transcriptional regulation of picrosides biosynthesis in Picrorhiza kurroa is completely unknown until Vashisht et al (2016) investigated complete spectrum of different transcription factors and discerned their association with picrosides biosynthesis [ 23 ].…”
Section: The Application Of Transcriptome In Chinese Medicinementioning
confidence: 99%